Role of nitric oxide in the periaqueductal gray in defensive behavior in mice: influence of prior local N-methyl-D-aspartate receptor activation and aversive condition - Nunes-de-Souza, Ricardo Luiz [UNESP]; Miguel, Tarciso Tadeu [UNESP]; Gomes, Karina Santos [UNESP]; Fugimoto, Juliana Sayuri [UNESP]; Mendes-Gomes, Joyce [UNESP]; Amaral, Vanessa Cristiane Santana [UNESP]; Carvalho-Netto, Eduardo Ferreira de (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), 2010)
Glutamate N-methyl-D-aspartate (NMDA) receptor activation within the dorsal column of the periaqueductal gray (dPAG) leads to antinociceptive, autonomic, and behavioral responses characterized as the fear reaction. Activation of NMDA receptors in the brain increases nitric oxide (NO) synthesis, and NO has been proposed to be a mediator of the aversive action of glutamate. This paper reviews a series of studies investigating the effects of neuronal NO synthase (nNOS) inhibition in the dPAG of mice in different aversive conditions. nNOS inhibition by infusion of Nω-propyl-L-arginine (NPLA) prevents fear-like reactions (e.g., jumping, running, freezing) induced by NMDA receptor stimulation within the dPAG and produces anti-aversive effects when injected into the same midbrain site in mice confronted with a predator. Interestingly, nNOS inhibition within the dPAG does not change anxiety-like behavior in mice exposed to the elevated plus maze (EPM), but it reverses the effect of an anxiogenic dose of NMDA injected into the same site in animals subjected to the EPM. Altogether, the results support a role for glutamate NMDA receptors and NO in the dPAG in the regulation of defensive behaviors in mice. However, dPAG nitrergic modulation of anxiety-like behavior appears to depend on the magnitude of the aversive stimulus.
Keywords: periaqueductal gray matter (PAG); NMDA receptors; neuronal nitric oxide synthase (nNOS); elevated plus maze (EPM); rat exposure test (RET); mouse